Penggunaan Pembelajaran ICT dalam Pelajaran PAI di MA Nihayatul Amal Rawamerta Karawang - Riska Syafarina; Oyoh Bariah; Nancy Riana (FONDATIA, 2022)
Technology in this digital era has become a very important study in teaching and learning activities in schools. So from now on, educators in schools need to be equipped with information and communication technology that will support the course of learning in e-learning in the future. Educational institutions strive to produce human resources who master the demands of the times, of course, know science and technology better and have professional qualities in their fields. Leads to Information and Communication Technology or what is called technology related to data retrieval, collection and storage and distributing it to a human audience which is presented in the form of software or other printed magazines. The purpose of this paper is to find out how proficient the teacher's activities at the Nihayatul Amal school are when using ICT learning in Islamic Religious Education subjects for students studying at school. To answer the problem, the researcher uses a literature study with qualitative research methods with a library research approach and is combined with the Filed Research approach, so that data collection uses observational studies and interviews so that the collected data is complementary to one another. The results obtained from this study are that ICT-based learning emphasizes the development of abilities (competencies) using multimedia in the learning process with certain standards so that the results can be felt directly by students. When viewed from the implementation, the ICT-based PAI learning process carried out at the Nihayatul Amal MA Rawamerta Karawang has been running and scheduled well. Based on the observations made by the researchers, the teacher was disciplined in teaching and the students were diligent in following the lesson. The ICT-based PAI learning process at SMP Negeri 2 Semarang has several components that must be fulfilled, namely learning planning, learning implementation, learning methods, types of multimedia or ICT use, learning methods and evaluation.